The Effectiveness of Ergonomic Training and Chiropractic Treatment in Industrial Workers with Nonspecific Chronic Neck Pain: A Randomized Controlled Trial - Deniz Balikçi; Beyzanur Dikmen Hoşbaş; Ömer Şevgin (Journal of Occupational & Environmental Medicine, 2026)
OBJECTIVE: To evaluate whether adding chiropractic treatment to ergonomic training improves pain, function, and sleep in industrial workers with chronic nonspecific neck pain. METHODS: Forty-five male industrial workers were randomized (15 per group) to ergonomic training plus chiropractic treatment (CTG), plus sham manipulation (SMTG), or alone (CG) for four weeks. Pain (VAS), biopsychosocial impact (BNQ), disability (NDI), and sleep quality (PSQI) were assessed before and after. The group × time interaction was the primary analysis. RESULTS: Significant interactions favoured CTG for VAS (p < 0.001) and BNQ (p = 0.004). NDI improved comparably in all groups (p = 0.591). PSQI was unchanged. CONCLUSIONS: Adding chiropractic treatment to ergonomic training reduced pain and biopsychosocial impact more than sham manipulation or training alone. Disability improved across all arms; sleep quality was unchanged.